Apuntes para una comprensión moral sobre los marcos de legalidad de la justicia y las víctimas en Colombia - Agudelo G., Diego (2023)
This article points out that Truth is the only road to reconciliation from the viewpoint of Christian moral and with it biblical hermeneutics is extremely useful. The main focus is on past special events occurred in Colombia and the enactment of many lawsintended to go in the direction in search for peace.